The Influence of Compensation and Performance Management on Talent Retention (Global Journal of Management and Business Research, 2016)
Retention of talented employees has been seen as the most significant to the development and achievement of the organisation's objectives in the competitive advantage. Owing to the competition for scarce skills, the retention of quality employees has emerged as the biggest challenge in human capital management in the Technical Vocational Education and Training (TVET) Colleges in South Africa. The objective of the present study is examined the influence of compensation and performance management as determinants of talent retention among academic staff in TVET Colleges in South Africa. This study employed the quantitative research method to investigate the influence of rewards on talent retention. This paper discussed retention practices that are compensation and performance since these factors affect talent retention. Results shows that the majority of employees are not satisfied with compensation, which results in considering leaving the Institution.
Keywords: compensation; performance management; retention; academic staff; recognition